2021
DOI: 10.1186/s13717-021-00304-6
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity influences avian feeding guild composition in urban landscapes: evidence from Bhubaneswar, India

Abstract: Background Habitat heterogeneity clearly distinguished in terms of availability of food and habitat resources and landscape features (natural or human-modified) play a crucial role in the avian species composition and population structure. To examine this, a study was carried out in Bhubaneswar, India, to understand the ecological niche distinction in birds based on habitat heterogeneity. Regular sampling was conducted in 30 sampling sites covering six different habitat types in a predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…There were similar ecological studies done in the agroforestry industry of Indonesia (Withaningsih and Alham, 2020), the urban landscapes of India (Panda et al, 2021) and Indonesian urban habitats (Pudyatmoko and Nurvianto, 2009) that showed high alpha diversity values. Similarly, bird density in different habitats of the TU was calculated and we found that higher density was observed in the forest habitat.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…There were similar ecological studies done in the agroforestry industry of Indonesia (Withaningsih and Alham, 2020), the urban landscapes of India (Panda et al, 2021) and Indonesian urban habitats (Pudyatmoko and Nurvianto, 2009) that showed high alpha diversity values. Similarly, bird density in different habitats of the TU was calculated and we found that higher density was observed in the forest habitat.…”
Section: Discussionsupporting
confidence: 56%
“…The least number of species was observed in the farm habitat. Several bird studies in urban gardens and parks have shown similar results, indicating that forest sections have a high diversity (Pudyatmoko and Nurvianto, 2009;Panda et al, 2021).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Feeding is an important activity in the life of the bird which is indispensible for their survival (Panda et al, 2021). Feeding guilds of birds provide insight into the ecology of species and are particularly useful in studies that assess specific ecological drivers of community change.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the carnivorous guild, such as the cattle egret and Red-wattled lapwing, were seen to eat on insects as well and were therefore classified as members of several guilds. Feeding is an important activity in the life of the bird which is indispensable for their survival [31]. Guild categorization among birds emphasizes the functional component of a community in an ecosystem.…”
Section: Resultsmentioning
confidence: 99%